Pengaruh Pendidikan dan Pengalaman Kerja Terhadap Kinerja Pegawai di Kantor Camat Tungkal Ilir Kabupaten Tanjung Jabung Barat - Saiyid Syekh (Universitas Batanghari, 2019)
Tungkal Ilir Sub District is one of the existing sub district in the regency administration of Tanjung Jabung Barat with an area of 100,31 km2. Sub-district office Tungkal Ilir , Tanjung Jabung Barat regency is located in the middle of Kuala Tungkal City and shelter 10 vilages. Based on linear regression analysis results show the equation Y = a + b1x1 + b2x2 + e with F tests the value of 0.001, a value of the t test for education and the value of 0.023 t test for the work experience of 0.001. Rated R square 29.3% 70.7%, while the rest describes other factors outside the model study and the value of R 0542, which means the correlation is being. The suggestion for a new researcher is hoped to use a most recent year and the interval years for the research in order the reaserch could describe a detail information about education and work experience.